Place of the antenatal care in the prevention of a premature delivery - B. Solange, Rasoanandrianina; A. Felanarivo, Razafindraibe; N. Zoly, Rakotomalala; Besaina, Rakotozanany; N. N, Rakotoarimalala; Fandresena,; J. Anderson, Randriambelomanana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Prematurity constitutes a source of morbidity and mortality neonatal. The objective of this study is to determine the place of the antenatal care in the prevention of a premature delivery. Methods: It is an analytical retrospective study, type “cases-controls” realized at CHU GOB, on 01 January to 31 December 2014. Results: The frequency of the premature delivery during the time of study was 6%. The risk factors significantly associated with the premature delivery were the primigestity, the primiparity and the antecedents of miscarriage. About the antenatal care, not followed pregnancy (p=0.01; OR=6.2; [IC 95% 1.3-29]), insufficient antenatal care (p<10-10; OR=6.7; [IC 95% 4.0-15]) and the antenatal care carried out in the basic health center (p=0.00002; OR=3,5; [IC 95% 1.8-6.5] influenced significantly with occurred of a premature delivery. While the realization of antenatal care 4 times and more and the realization of antenatal care at Universities Hospital Center protected the patients in occurred of a premature delivery. Conclusions: The improvement of antenatal care’s quality and the medical infrastructures at basic health center, as well as the sensibilization to the population on the importance of antenatal care constitutes a priority in order to prevent effectively occurred of a premature delivery.